Does Brand Image affect the Purchase Decision of the ASUS Brand Laptop among Students? - Indah Wati; Soemarno Hidayatullah. S; Muhlis; Eva Yuniarti Utami; Ilma Wulansari Hasdiansa (Global Research Collaboration, 2023)
This research aims to find out whether brand image among students influences the decision to purchase Asus brand laptops. The sample in this research was consumers using Asus laptops, namely 96 people who were accidentally met by the researchers and deemed suitable as respondents, so the accidental sampling method was used. Data collection was carried out using questionnaires, interviews, and documentation methods. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS) v.20 and hypothesis testing using the t test and F test. The results of the research show that partially the product image has a positive and significant influence on purchasing decisions regarding Asus laptops among students. Brand image consisting of company image, user image and product image simultaneously has a positive and significant influence on the decision to purchase Asus laptops among students. This means that the brand image of Asus laptops is one of the factors in consumer purchasing decisions.